Prediction of Neural Diameter From Morphology to Enable Accurate Simulation - Reed, Jonathan D.; Blackwell, Kim T. (Frontiers in Neuroinformatics, 2021)
Accurate neuron morphologies are paramount for computational model simulations of realistic neural responses. Over the last decade, the online repository NeuroMorpho.Org has collected over 140,000 available neuron morphologies to understand brain function and promote interaction between experimental and computational research. Neuron morphologies describe spatial aspects of neural structure; however, many of the available morphologies do not contain accurate diameters that are essential for computational simulations of electrical activity. To best utilize available neuron morphologies, we present a set of equations that predict dendritic diameter from other morphological features. To derive the equations, we used a set of NeuroMorpho.org archives with realistic neuron diameters, representing hippocampal pyramidal, cerebellar Purkinje, and striatal spiny projection neurons (SPNs). Each morphology is separated into initial, branching children, and continuing nodes. Our analysis reveals that the diameter of preceding nodes, Parent Diameter, is correlated to diameter of subsequent nodes for all cell types. Branching children and initial nodes each required additional morphological features to predict diameter, most commonly path length to soma and longest path to terminal end. Model simulations reveal that membrane potential response with predicted diameters was similar to the original response for several tested morphologies. Predictions that use the original diameter of initial nodes improved the membrane potential response, so that the difference from the simulations of the original morphology was reduced to an average of 20%. We provide our open source software to extend the utility of available NeuroMorpho.org morphologies, and suggest predictive equations may supplement morphologies that lack dendritic diameter and improve model simulations with realistic dendritic diameter.